2016
DOI: 10.1016/j.talanta.2016.04.044
|View full text |Cite
|
Sign up to set email alerts
|

Classification of biodiesel and fuel blends using gas chromatography – differential mobility spectrometry with cluster analysis and isolation of C18:3 me by dual ion filtering

Abstract: Fatty acid alkyl esters (FAAEs) were determined at 10-100mg/L in biodiesel and blends with petrodiesel without sample pre-treatment using gas chromatography with a tandem differential mobility detector. Selectivity was provided through chromatographic separations and atmospheric pressure chemical ionization reactions in the detector with mobility characterization of gas ions. Limits of detection were ~0.5ng with an average of 2.98% RSD for peak area precision, ≤1.3% RSD for retention time precision, and ≤9.2% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…Quantitative abundance measures are frequently needed for a specific application, or chemical detection is required in the ambient gas phase. One notable category of detection methods for these gas phase detection strategies is I on M obility S pectrometry (IMS) [68], and these techniques are widely employed today in multiple industries, such as: space exploration [9], the food and beverage industry [1012], metabolomics for health diagnostics [13, 14] and fuel applications [15]. Used widely since the 1970’s, the technique uses ion mobility in an electric field as the basis of chemical separation and detection.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative abundance measures are frequently needed for a specific application, or chemical detection is required in the ambient gas phase. One notable category of detection methods for these gas phase detection strategies is I on M obility S pectrometry (IMS) [68], and these techniques are widely employed today in multiple industries, such as: space exploration [9], the food and beverage industry [1012], metabolomics for health diagnostics [13, 14] and fuel applications [15]. Used widely since the 1970’s, the technique uses ion mobility in an electric field as the basis of chemical separation and detection.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of chromatographic and spectroscopic techniques are used to assess the quality of biodiesel, including thin layer chromatography, , gas chromatography with flame ionization detector (GC-FID), gas chromatography–mass spectrometry, headspace-based gas chromatography, gas chromatography-differential mobility spectrometry with cluster analysis, high-performance liquid chromatography, gel permeation chromatography, supercritical fluid chromatography, near-infrared spectroscopy, , Fourier-transform spectroscopy, , Raman spectroscopy, 13 C NMR, H NMR, and sequential/flow injection analysis (SIA/FIA). , …”
Section: Introductionmentioning
confidence: 99%
“…The results showed that it is possible to develop a reliable and rapid methodology to identify used vegetable oils with raw materials in biodiesel production by applying the unsupervised techniques of multivariate analysis to the data. HCA and PCA were also used in the analysis of gas chromatography as a tool to classify/analyze biodiesels for chemical information. , Multivariate analysis was also used to predict water content in biodiesel, to monitor and quantify transesterification reaction, in H NMR spectra of fatty esters and biodiesels to infer the corresponding cetane number, , to associate and discriminate samples for potential use in forensic and environmental applications, and to classify biodiesel/diesel blends. , Recently, the change of the dielectric property was found to be consistent with the Rancimat conductivity, infrared peak area, ultraviolet absorbance, and the residual mass during the degradation process …”
Section: Introductionmentioning
confidence: 99%